2018
DOI: 10.1111/jocn.14243
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perceptions of family‐centred support and their associations with the mother–nurse relationship in the neonatal intensive care unit

Abstract: Clear visual information materials might promote better maternal understanding of their infants, help in acquisition of parent-crafting skills and improve mother-nurse collaboration, with the result that mothers are better able to care for their infants autonomously at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…In keeping with other studies, we also found that involvement in care led to greater maternal confidence in providing care to the infant [3639]. The way the FCC model is designed at RML Hospital, parents are provided with clear audio-visual information and repeated interactive education, which has built their capacity to perform care activities and, thus, their confidence.…”
Section: Discussionsupporting
confidence: 87%
“…In keeping with other studies, we also found that involvement in care led to greater maternal confidence in providing care to the infant [3639]. The way the FCC model is designed at RML Hospital, parents are provided with clear audio-visual information and repeated interactive education, which has built their capacity to perform care activities and, thus, their confidence.…”
Section: Discussionsupporting
confidence: 87%
“…Clinicians recognise the significant roles families play in the NICU, for example in providing information and purchasing medicine and supplies to support the care of their critically ill loved ones. This finding resonates with the concept of FCC practiced in Japan [ 29 ]. However, families were seen to be helpful in complementing the efforts of clinicians in the NICUs, in most cases, to provide quality care at their best.…”
Section: Discussionsupporting
confidence: 83%
“…The practice of FCC in many countries has been reported. For instance, in Asia, the main concepts adopted were support, visual information, collaboration, partnerships and mutual trust [13][14][15]. The fundamental concepts of FCC on the American continent are information sharing (education and communication), participation (parental involvement), respect and dignity and shared decision-making [16,17].…”
Section: Introductionmentioning
confidence: 99%
“… 44 Another cross-sectional study reported that mothers’ perceptions of FCC, including KMC, mothers’ participation in activities such as feeding, bathing, and changing diapers were positive, and mothers felt that nurses paid enough attention to their feelings. 38 …”
Section: Resultsmentioning
confidence: 99%
“… 32 Also, FCC was directly associated with mothers’ abilities to cope with special needs and situations. 38 …”
Section: Resultsmentioning
confidence: 99%